1997
DOI: 10.1097/00000539-199706000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Intubation Using Alfentanil and No Muscle Relaxant

Abstract: Administration of alfentanil followed by propofol intravenously (IV) without neuromuscular blockade for induction of anesthesia provides adequate conditions for tracheal intubation. Other hypnotic drugs have not been thoroughly investigated in this regard. Accordingly, 140 ASA physical status I and II premedicated outpatients were randomly assigned to one of seven groups (n = 20/group). Patients in Groups I-VI received alfentanil 40 microg/kg followed by etomidate 0.3 mg/kg, propofol 2 mg/kg, or thiopental 4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Remifentanil administration (1 to 3 mcg/kg) without propofol can lead to muscle stiffness (i. e. , difficult ventilation with a mask) depending on the drug dosage and the speed of administration ( 12 , 13 ), but if administered in combination with propofol, muscle stiffness will rarely occur ( 20 ). Similarly, alfentanil (40 mcg/kg) in combination with propofol does not lead to significant muscle stiffness ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remifentanil administration (1 to 3 mcg/kg) without propofol can lead to muscle stiffness (i. e. , difficult ventilation with a mask) depending on the drug dosage and the speed of administration ( 12 , 13 ), but if administered in combination with propofol, muscle stiffness will rarely occur ( 20 ). Similarly, alfentanil (40 mcg/kg) in combination with propofol does not lead to significant muscle stiffness ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The laryngoscopy and subsequent endotracheal intubation induce strong nociceptive stimuli resulting numerous responses for example, motor response, characteristic electroencephalographic evidence of central nervous system stimulation or stimulation of the sympathetic nervous system manifested by increased arterial pressure and accelerated HR. [ 11 12 ] In our study, patients intubated by clinical judgment showed higher mean values of mean arterial pressure and HR during and after intubation in comparison to the patients who were intubated under guidance of neuromuscular monitoring ( P < 0.05). It seems that in patients with incomplete neuromuscular block, laryngoscopy and intubation cause stronger nociceptive stimulation, hence a stronger reflex cardiovascular reaction.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, laryngoscopy was performed 7 min after fentanyl injection, as some authors have described that the peak action of fentanyl comes after 7 min. [1314] However, in many studies as our study laryngoscopy was performed earlier. Kwon et al .…”
Section: Discussionmentioning
confidence: 98%